Proceedings of the 2020 Genetic and Evolutionary Computation Conference Companion 2020
DOI: 10.1145/3377929.3389901
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive reinforcement learning through evolving self-modifying neural networks

Abstract: The adaptive learning capabilities seen in biological neural networks are largely a product of the self-modifying behavior emerging from online plastic changes in synaptic connectivity. Current methods in Reinforcement Learning (RL) only adjust to new interactions after reflection over a specified time interval, preventing the emergence of online adaptivity. Recent work addressing this by endowing artificial neural networks with neuromodulated plasticity have been shown to improve performance on simple RL task… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Synaptic plasticity is a powerful mechanism for unsupervised learning in neural networks, inspired by learning processes in the biological brain [1,2,3,4,5]. This process has been incorporated into spiking and artificial neural networks to enable intra-lifetime learning [8,9,10,11,12,13]. However, in this work it was shown that plastic ANNs struggle to generalize their behavior beyond the training time horizon.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Synaptic plasticity is a powerful mechanism for unsupervised learning in neural networks, inspired by learning processes in the biological brain [1,2,3,4,5]. This process has been incorporated into spiking and artificial neural networks to enable intra-lifetime learning [8,9,10,11,12,13]. However, in this work it was shown that plastic ANNs struggle to generalize their behavior beyond the training time horizon.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, these methods, as a product of not using backpropagated gradients, do not perform backpropagation through time, and hence time-dependent parameters, like synaptic plasticity, do not require immense compute time. Particularly in the context of synaptic plasticity, some situations display evolutionary algorithms outperforming gradient-based approaches in both learned performance and in training time [25,26].…”
Section: Evolutionary Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also more recent works on self-modifying NNs. Neuromodulated plasticity is a Hebbian-style self-modification (Miconi et al, 2018;Schmidgall, 2020;Najarro & Risi, 2020) which also makes use of outer products to generate a modulation term which is added to the base weights. The corresponding computations can also be interpreted as key/value/query association operations.…”
Section: Related Workmentioning
confidence: 99%
“…This is primarily due to the use of spikes for information transmission, which does not naturally lend itself toward being used with backpropagation. To circumvent this challenge, a wide variety of learning algorithms have been proposed including Spike-Timing Dependent Plasticity (STDP) (Masquelier et al, 2009;Bengio et al, 2017;Kheradpisheh et al, 2018;Mozafari et al, 2018), ANN to SNN conversion methods (Diehl et al, 2015;Rueckauer et al, 2017;Hu et al, 2018), Eligibility Traces (Bellec et al, 2020), and Evolutionary Strategies (Pavlidis et al, 2005;Carlson et al, 2014;Eskandari et al, 2016;Schmidgall, 2020). However, a separate body of literature enables the use of backpropagation directly with SNNs typically through the use of surrogate gradients (Bohte et al, 2002;Sporea and Grüning, 2012;Lee et al, 2016;Shrestha and Orchard, 2018).…”
Section: Introduction and Related Workmentioning
confidence: 99%